2018
DOI: 10.1386/jaah.9.1.25_1
|View full text |Cite
|
Sign up to set email alerts
|

Connecting reminiscence, art making and cultural heritage: A pilot art-for-dementia care programme

Abstract: Incidence of dementia in Singapore is increasing and strategies to care for people with dementia are necessary. Let's Have Tea at the Museum is a pilot participatory visual art programme designed for clients at an Alzheimer's Disease Association (ADA) Singapore day care centre. The programme, which combines reminiscence with artmaking, aims at enabling participants to further explore the heritage collection at the Peranakan Museum to reawaken memories and promote personal expression. This study involved eight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…Furthermore, it was identified that it was less about the sophistication of a skill and more about one's willingness to try something new, such as in the case of not being required to be a good singer to partake in singing activities (Unadkat et al, 2017). Overall, the experience of new learning led to improved confidence and often surprise at their potential to learn ( Tan, 2018), given that dementia is typically associated with loss, rather than the acquisition of new knowledge. Therefore, participatory arts are effective because participants are not being restricted by dementia assumptions and stigma but can freely explore their abilities and boundaries through cognitive stimulation.…”
Section: C) 'In the Moment'mentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, it was identified that it was less about the sophistication of a skill and more about one's willingness to try something new, such as in the case of not being required to be a good singer to partake in singing activities (Unadkat et al, 2017). Overall, the experience of new learning led to improved confidence and often surprise at their potential to learn ( Tan, 2018), given that dementia is typically associated with loss, rather than the acquisition of new knowledge. Therefore, participatory arts are effective because participants are not being restricted by dementia assumptions and stigma but can freely explore their abilities and boundaries through cognitive stimulation.…”
Section: C) 'In the Moment'mentioning
confidence: 99%
“…All 26 reviewed papers made a varying level of reference to the underlying social benefits of participatory arts, which were viewed as an effective way to reduce social isolation, both for people with dementia and their carers (Camic et Tan, 2018). Laughter was also capable of dissolving dementia-related tensions and moments of cognitive difficulty, giving an impression of a non-judgemental shared attitude (Selberg, 2015).…”
Section: The Group A) Social Cohesion and Togethernessmentioning
confidence: 99%
See 1 more Smart Citation
“…The Arts and Dementia programme offered by the Alzheimer’s Disease Association (ADA), Singapore, was built upon a pilot programme, Let’s Have Tea at the Museum , described in Tan’s (2018) study. The Arts and Dementia programme is a series of community-based creative art activities, which include art-appreciation, art-making, singing, movement and dance and music.…”
Section: Arts and Dementia Programmementioning
confidence: 99%
“…With an understanding that engaging in participatory arts can empower and enhance psychosocial and emotional wellbeing amongst older adults with dementia (McLean et al 2011;Tan 2018;Grant et al 2012), this study expands on existing life review approaches to incorporate the elements of art-making. Although most life reviews were implemented through verbal interviews or written accounts, there are two studies that support conducting life review through creative expressions for older adults (Bohlmeijer et al 2005;Misluk and King 2017).…”
Section: Life Review and Art Participation For Older Adults With Dementiamentioning
confidence: 99%